Dorzagliatin shows potential in preventing cognitive impairment in diabetes: evidence from Mendelian randomization analysis and animal study - Ni, Jiangxia; Wang, Ke; Feng, Lingge; Wang, Chuyi; Li, Changhong; Chen, Yelin; Chen, Li (Frontiers in Endocrinology, 2026)
AimDorzagliatin is a glucokinase (GK) activator, restoring glucose homeostasis in type 2 diabetes. We investigated the effects of dorzagliatin on cognitive traits using Mendelian randomization (MR), with validation in a spontaneous diabetic rat model.MethodsA two-sample MR study was conducted to investigate the causal effects of GK activation on neurodegenerative traits. Utilizing genome-wide association study summary statistics, we selected independent genetic variants of GCK (encodes GK) associated with lower HbA1c as instrumental variables to mimic GK activation. An animal validation study was further performed. Goto Kakizaki rats and Wistar rats were treated with vehicle or low-dose dorzagliatin (8mg/kg, i.g, bid, below the therapeutic level) for 36 weeks. Morris water maze (MWM) test, western blot analyses were carried out to investigate the neuroprotective effects of dorzagliatin and explore the potential mechanisms.ResultsGenetically mimicked GK activation causally decreased risk of memory loss (OR 0.21 per 1% lower HbA1c, 95% CI 0.05-0.91) and was associated with higher scores of prospective memory task, symbol digit substitution task and intelligence. MR results also implied that GK activation had cognitive protective effects not solely attributed to glucose-lowering. Low-dose dorzagliatin treatment in young Goto Kakizaki rats prevented spatial memory impairment occurred in adulthood in the MWM test. It also significantly prevented the reduced expression of insulin receptors, glucose transporters, and synaptic proteins in the brains of Goto Kakizaki rats.ConclusionsDorzagliatin protects against cognitive impairment under diabetes conditions. Maintaining glucose homeostasis directly regulates insulin pathway and glucose uptake, as well as enhances neurotransmission processes in the hippocampus. These findings not only highlight dorzagliatin as a promising therapeutic option for preventing diabetes-associated cognitive decline but also provide critical mechanistic insights into the role of GK modulated glucose homeostasis in preserving brain function, offering a potential translational strategy for clinical intervention.